The Literature of the Crisis - Watkins, Myron W. (Quarterly Journal of Economics, 1933)
Journal Article The Literature of the Crisis Get access Myron W. Watkins Myron W. Watkins New York University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 3, May 1933, Pages 504–532, https://doi.org/10.2307/1883983 Published: 01 May 1933